The religious extremism and terrorism is the basis of interethnic tensions - Kusbekov, D.K.; Mashabayev, A.Zh. (KSU publ, 2015)
This article deals with the problems of religious extremism and terrorism in the modern society. Within the article are characterized social and legal consequences of this negative phenomenon . Noted that the violence is the main tool for extremists. The cause of religious extremism and terrorism is seen in the unresolved social and political problems. The author focuses on the fact that the collaboration work of all level organizations is necessary in fighting against religious extremism and terrorism in modern conditions.
Keywords: religion; Religious extremism; terrorism, crime; society; violence; conflictology; philosophy; politics; The Republic of Kazakhstan; criminology; international conflict